Morphological variation of the leaves of Aechmea distichantha Lem. plants from contrasting habitats of a Chaco forest: a trade-off between leaf area and mechanical support - Cavallero, Laura (2011)
Several authors have reported phenotypic plasticity for bromeliad plants growing in contrasting habitats. Morphological and physiological differences at the leaf level seem to be an adaptation to water and light use, but there is also a compromise between carbon gain and the costs of sustaining static and dynamic loads. We hypothesized that plastic responses to habitat at the leaf level represent a trade-off between photosynthetic area for light capture and mechanical support. In this study, we measured morphological and architectural variables on central and basal leaves of Aechmea distichantha plants from understory and forest edges, as well as anatomical variables for plants from each habitat. Understory plants had longer leaves, larger blade area and greater length/width ratios than forest-edges plants. Blades of understory plants were less erect, less succulent, had thicker fiber tissue surrounding the vascular bundles and higher curvature index than blades of forest-edge plants. Thus, understory plants increased their flexural stiffness by modifying their tissue structure as well as the shape of their leaves. On the other hand, blades of forest-edge plants had higher stomatal density and higher trichome density on their adaxial side than understorey plants. These patterns could be adaptations to higher gas exchange and to reduce vulnerability to photoinhibition in sun than in shade plants. Finally, most of the morphological and architectural variables were significantly different between positions. These results support our view that there is a trade-off at the leaf level between photosynthetic leaf area (for light capture and water use) and mechanical support.